Oral administration of tocotrienol ameliorates lead-induced toxicity in the rat brain - Noor Azliza Wani Aa,; Zar, Chi Thent; Mohamad Fairuz Yahaya,; Teoh, Seong Lin; Taty Anna K,; Azian Abd Latiff, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
The occurrence of severe lead (Pb) poisoning has risen in certain countries. There is increasing evidence that chronic lead exposure disturbs the prooxidant: antioxidant balance in the brain tissue and alters brain histology. The present study observed the antioxidant effect of tocotrienol-rich fraction (TRF) on brain tissues of the experimental rats following lead poisoning. Eighteen (n=18) male Sprague-Dawley rats, 6-weeks old, were randomly divided into control (CTRL) group and experimental groups; fed with 0.2% w/v lead acetate, as PB2 group; and fed with 0.2% w/v lead acetate and daily TRF supplementation (200 mg/kg body weight) as PB2T group. The experiment was conducted for 30 days. At the end of the study, the brain tissues were harvested and histopathological changes of the hippocampal region were observed. Biochemical findings such as brain lead, TRF and malondialdehyde (MDA) levels, and erythrocyte superoxide dismutase (SOD) activity were determined. It was observed that atypical apoptotic-like and disorganized neurons were present in the hippocampal region of the untreated PB2 group compared to PB2T group. Biochemical parameters showed a significant decrease (p < 0.05) in brain lead level in PB2T compared to PB. Even though no significant difference (p > 0.05) was obtained for MDA level, there was a significant increase (p < 0.05) in the erythrocyte SOD activity in PB2T compared to PB2 and CTRL. Supplementation with TRF improved histopathological changes in the brain tissues caused by lead exposure in drinking water by reducing lead accumulation in the brain of experimental rats.